(untitled) (Global Journal of Science Frontier Research, 2022)
Heat treatment is effective for removing petroleum hydrocarbons from soil. However, high heat reduces the fertility of soils. This study determined the effect of temperature, and crude oil and salt additions on the fertility of four soils. Effects were assessed immediately after thermal treatment and following an equilibration/stabilization period. Soils were heated at four controlled temperatures (65, 300, 425, and 550°C) and also in an uncontrolled smoldering device, with 0 or 50 g kg -1 oil added and with 3 levels of salt solution added (0, 1, or 3 ms cm -1 ). Soils were ’rapidly weathered’ via wet / dry cycles at 37°C for five weeks. Initial changes in soil fertility were extreme enough to inhibit plant growth. Soil pH values were positively related to temperature, exceeding pH 8.5 at 550°C. The severity of changes was markedly reduced following incubations, showing that post heat treatment fertility will rebound with time and water.